P156 Maintaining patients with idiopathic pulmonary fibrosis (ipf) on antifibrotic therapy; the nurses' challenge. (15th November 2017) - Burge, GA; Alldrick, H; Briggs, E; Neighbour, K; Burge, PS; Walters, GI
Abstract : Pirfenidone and nintedanib are the first licensed drugs for IPF. Both reduce the rate of disease progression but have significant intolerability issues limiting long-term use. This study aims to identify areas where changes in practice might improve outcomes. We compared baseline characteristics of disease severity with the reasons for stopping treatment and the proportion stopping treatment within the first 4 weeks, for all patients from our centre up to December 2016, including those receiving treatment on a named patient basis. Data was available for 150/153 patients started on pirfenidone and 56/57 on nintedanib. Table 1 compares patients who were dispensed treatment but never took it, patients who stopped after the first prescription, and those continuing treatment. 8 patients consented to treatment but never took the drug; they were older and had less advanced disease. 39 patients stopped treatment after the first prescription; they had slightly more advanced disease, and had a longer interval between drug delivery and the first nurse (60.7 SD 57 days vs. 45.4 SD 30; (p=0.032), and more often had a shared care arrangement, but did not have a lower BMI. Photosensitivity for pirfenidone and diarrhoea for nintedanib were usually managed by treatment and were uncommon reasons for stopping antifibrotic therapy, which was more often related to upper GI intolerance and disease progression. Conclusion: Patients stopping antifibrotic treatment early cannot be identified from baseline data but can be reduced by intensive nursing support. Prescribing centre based ILD-CNS's should be responsible for early treatment tolerability and aim to see patients monthly until established on treatment. Uncertain delays between prescription and drug delivery make this more difficult.